(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The technical process of purified KMTs includes the following steps: Preparation of products and solutions; Extraction; Squeeze; Drying of purified Na-KMTs; Grinding; Packaging of the finished product; Cleaning the used solution. In this section, research has been conducted on the production of several brands of high-purity E-466 for the pharmaceutical and medical industries from fibrous waste from ginneries and cellulose obtained from pavlonia tree and banana stalks.